Associate Professor Dr. Ramadhansyah Putra Jaya produces porous concrete ready within 24 hours - Hafizatulazlin, Abdul Aziz (2023)
PEKAN, 28 December 2022 – Generally, the existing porous concrete cannot be used immediately after construction.